CLICK, LEARN, REMEMBER: Digital Tools for Memorizing the Quran - Busro, Busro; Hakim, Rizal (Ulul Albab: Jurnal Studi Islam, 2025)
This study aims to evaluate the effectiveness of the Cinta Quran application’s interactive features in supporting the Quran memorization process, focusing on user motivation, engagement, and accessibility. The research is significant in addressing the growing role of digital tools in religious education and their potential to improve spiritual practices. The study employs a qualitative descriptive approach with a case study method. Data were collected through digital observation of the application's features and user reviews on the PlayStore. The analysis was conducted thematically to identify key patterns and insights. The study reveals that features such as flexible quiz modes, audio playback, and color-coded visualization significantly enhance structured and personalized users’ learning experiences. These features increase motivation and engagement of users from diverse demographics. However, technical challenges, including audio issues, application crashes, and slow loading times, were identified as barriers to accessibility and reliability. The findings contribute to the religious education field by demonstrating how interactive digital tools can effectively support the Quran memorization and broader spiritual practices. They also offer practical insights for developers to improve inclusivity and accessibility in religious applications. This article provides a novel perspective on integrating interactive features and addressing technical challenges in digital tools for religious education. Its focus on the Cinta Quran app offers unique insights into how personalized and adaptive technology can enhance user experience and support spiritual practices in the digital era.